The Effect of the plant Adiantum philippense Extracts on Biofilms Formation and Adhesion to Shigella flexneri: A Predictive Modelling Approach (Journal of Biochemistry, Microbiology and Biotechnology, 2021)
In the quest for novel bioactive metabolites, which can also be used as therapeutic agents, Adiantum philippense (A. philippense), an ethnomedically important fern, has become a fascinating herb. In this study, the predictive mathematical modelling of A. philippense crude extract was tested against Shigella flexneri, a common food pathogen for its phytochemical constituents, antagonistic ability, and effect on bacterial adhesion and biofilm formation was calculated. Various kinetics models such as Von Bertalanffy, Baranyi-Roberts, modified Schnute, Modified Richards, Modified Gompertz, Modified Logistics and latest Huang were used to get values for the above kinetic constants or parameters. modified Gompertz of the entire model was found to be the best model with the highest adjusted R2 value and lowest RMSE value. The accuracy and bias factors values were close to unity (1.0). The maximum specific growth rate (mmax (h-1) for S. flexneri treatment with A. philippense extract was significantly much lower (p
Keywords: Shigella flexneri; Modified Gompertz; Adiantum philippense; Biofilm; modelling